Effects of dexamethasone on growth, viability and ultrastructure of bovine secondary follicles cultured in vitro. Issue 6 (27th December 2020) - Barroso, P.A.A.; Paulino, L. R F.M.; Silva, B.R.; Vasconcelos, G.L.; Gomes, D.S.; Lima Neto, M.F.; Silva, A.W.B.; Souza, A.L.P.; Donato, M.A.M.; Peixoto, C.A.; Silva, J.R.V.
Summary: This study aimed to evaluate the effects of dexamethasone on development, viability, antrum formation and ultrastructural integrity of bovine secondary follicles cultured in vitro for 18 days. Bovine ovaries were obtained from slaughterhouses and secondary follicles of ~150–200 µm diameter were isolated and cultured in the laboratory in TCM-199 + alone or supplemented with different concentrations of dexamethasone (1, 10, 100 and 1000 ng/ml). Follicle viability was evaluated after the culture period, using calcein-AM (viable) and ethidium homodimer (nonviable). Follicle diameters and antrum formation were evaluated at days 0, 6, 12 and 18. Before or after in vitro culture, follicles were fixed for histological and ultrastructural analysis. Follicle diameters were evaluated using analysis of variance and Kruskal–Wallis test, while chi-squared test was used to evaluate the percentage of viable follicles and antrum formation ( P < 0.05). Follicles cultured for 6 days with all treatments increased their diameters significantly, but there was no significant difference between treatments at the end of the culture period. In vitro cultured follicles showed antral cavity formation at the end of the culture period, but no influence of dexamethasone was seen. Ultrastructural analysis showed that follicles cultured with dexamethasone (1, 10, 100 and 1000 ng/ml) had well preserved granulosa cells. However, oocytes from follicles cultured with 10, 100 or 1000 ng/ml dexamethasone showed signs of degeneration. It can be concluded that follicles cultured in vitro in the presence of dexamethasone demonstrated continuous in vitro growth, but oocytes from follicles cultured with 10, 100 or 1000 ng/ml dexamethasone had poor ultrastructure.